2018
DOI: 10.1007/s10453-018-9508-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of meteorological parameters on Alternaria and Cladosporium fungal spore concentrations in Beja (Southern Portugal): preliminary results

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media B.V., part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…However, annual Cladosporium SIn averages over 1993-2009 at 10 out of 12 stations in the Iberian Peninsula had lower values: 54,459-238,214 Spores day m -3 , with higher values in Merida (579,953 Spores day m -3 ) and Sevilla (933,485 Spores day m -3 )(Aira et al 2012). Annual SIn, lower than 3-month SIn averages in Denmark, were reported for Southern Portugal(Almeida et al 2018) and Madeira Island(Sousa et al 2016) at 92,351 -123,863 Spores day m -3 , and for the Western Thrace region in Greece at 120,464 Spores day m -3(Katotomichelakis et al 2016). Cladosporium SIn values close to or lower than the 3-month Copenhagen Cladosporium SIn were reported for northern Poland (annual SIn = 392,670 Spores day m -3 )(Bednarz and Pawlowska 2016) and North-West Morocco (SSIn 296,707 -417,929 Spores day m -3 )(Bardei et al 2017), whereas annual SSIn reported for western and eastern Poland were at least twice higher than the 3-month Copenhagen Cladosporium SIn(Kasprzyk et al 2016;Weryszko-Chmielewska et al 2018).…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…However, annual Cladosporium SIn averages over 1993-2009 at 10 out of 12 stations in the Iberian Peninsula had lower values: 54,459-238,214 Spores day m -3 , with higher values in Merida (579,953 Spores day m -3 ) and Sevilla (933,485 Spores day m -3 )(Aira et al 2012). Annual SIn, lower than 3-month SIn averages in Denmark, were reported for Southern Portugal(Almeida et al 2018) and Madeira Island(Sousa et al 2016) at 92,351 -123,863 Spores day m -3 , and for the Western Thrace region in Greece at 120,464 Spores day m -3(Katotomichelakis et al 2016). Cladosporium SIn values close to or lower than the 3-month Copenhagen Cladosporium SIn were reported for northern Poland (annual SIn = 392,670 Spores day m -3 )(Bednarz and Pawlowska 2016) and North-West Morocco (SSIn 296,707 -417,929 Spores day m -3 )(Bardei et al 2017), whereas annual SSIn reported for western and eastern Poland were at least twice higher than the 3-month Copenhagen Cladosporium SIn(Kasprzyk et al 2016;Weryszko-Chmielewska et al 2018).…”
contrasting
confidence: 60%
“…Seasonal length, however, does not appear to correlate with Alternaria spore abundance: relatively short Alternaria seasons in northern locations can have higher Seasonal Spore Integral (SSIn) values than those in locations with longer seasons (Skjøth et al 2016). A similar geographical pattern seems to be true for Cladosporium: longer seasons in the South with bi-modal distributions and lower SSIn (Katotomichelakis et al 2016;Sousa et al 2016;Bardei et al 2017;Almeida et al 2018) than in central European locations with mono-modal Cladosporium distributions (Chrenová et al 2004;Kasprzyk et al 2016;Sindt et al 2016), although Cladosporium incidence and seasonality are currently underreported.…”
mentioning
confidence: 98%
“…and Cladosporium spp. and negative correlation with humidity (52). In this study, the greatest release of fungal aerosols occurred in the cold season while the minimum release occurred in the warm season, which is consistent with the results of studies by Pasquarella et al (2) and Niazi et al (14).…”
Section: Discussionsupporting
confidence: 93%
“…The authors attributed this result to increased wet deposition rates. In contrast, temperature was positively correlated with both Alternaria and Cladosporium spore levels measured over the course of two years in the atmosphere in the same study [48]. The day-to-day patterns are related to the phenology of the source communities, while diurnal fluctuations may better reflect physiological characteristics of the organisms and their tolerance to environmental stressors.…”
Section: Relationships Of Bioaerosols and Environmental Factors Including Particulate Mattermentioning
confidence: 83%